2007
DOI: 10.1152/ajpheart.00819.2007
|View full text |Cite
|
Sign up to set email alerts
|

Protective roles of adenosine A1, A2A, and A3receptors in skeletal muscle ischemia and reperfusion injury

Abstract: Although adenosine exerts cardio-and vasculoprotective effects, the roles and signaling mechanisms of different adenosine receptors in mediating skeletal muscle protection are not well understood. We used a mouse hindlimb ischemia-reperfusion model to delineate the function of three adenosine receptor subtypes. Adenosine A(3) receptor-selective agonist 2-chloro-N(6)-(3-iodobenzyl)adenosine-5'-N-methyluronamide (Cl-IBMECA; 0.07 mg/kg ip) reduced skeletal muscle injury with a significant decrease in both Evans b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 41 publications
0
70
0
1
Order By: Relevance
“…In transfected CHO cells, the ability of both recombinant hA 3 ARs to inhibit cAMP accumulation and endogenous A 3 ARs in RBL-2H3 to stimulate PLC is abolished by pretreatment with pertussis toxin, suggesting a functional coupling of this G i protein receptor (Ali et al, 1990;Zhou et al, 1992;Varani et al, 2000). Furthermore, A 3 ARs signaling could increase phosphatidylinositol-specific PLC activity (Ali et al, 1990;Ramkumar et al, 1993;Abbracchio et al, 1995;Zheng et al, 2007) and cause the release of Ca 2+ from intracellular stores in different cellular models Merighi et al, 2001;Englert et al, 2002;Fossetta et al, 2003;Shneyvays et al, 2004Shneyvays et al, , 2005Kim et al, 2012). In a broad study of site-directed mutagenesis of the A 3 AR, the mutation of the highly conserved tryptophan (W6.48) in the transmembrane domain 6 of GPCRs was first characterized .…”
Section: Intracellular Pathways Regulated By the Amentioning
confidence: 99%
See 1 more Smart Citation
“…In transfected CHO cells, the ability of both recombinant hA 3 ARs to inhibit cAMP accumulation and endogenous A 3 ARs in RBL-2H3 to stimulate PLC is abolished by pretreatment with pertussis toxin, suggesting a functional coupling of this G i protein receptor (Ali et al, 1990;Zhou et al, 1992;Varani et al, 2000). Furthermore, A 3 ARs signaling could increase phosphatidylinositol-specific PLC activity (Ali et al, 1990;Ramkumar et al, 1993;Abbracchio et al, 1995;Zheng et al, 2007) and cause the release of Ca 2+ from intracellular stores in different cellular models Merighi et al, 2001;Englert et al, 2002;Fossetta et al, 2003;Shneyvays et al, 2004Shneyvays et al, , 2005Kim et al, 2012). In a broad study of site-directed mutagenesis of the A 3 AR, the mutation of the highly conserved tryptophan (W6.48) in the transmembrane domain 6 of GPCRs was first characterized .…”
Section: Intracellular Pathways Regulated By the Amentioning
confidence: 99%
“…Interestingly, the A 3 AR agonist is a prime candidate for pharmacologic intervention in the first few hours postinjury based on several working hypotheses concerning its mechanism of protection. The pathway involves PLC b2/b3, which in turn activates PKC via diacylglycerol (Zheng et al, 2007). PKC has been shown to activate K ATP channels and cause protection.…”
Section: F Muscle Systemmentioning
confidence: 99%
“…There is evidence for an anti-inflammatory role for A 1 R in lung 5 , liver 15 , kidney 16 , heart 17 , intestine 18 and skeletal muscle. 19 However, other studies have suggested that A 1 R antagonism has beneficial effects in lung and heart IR models. 10,20 In the current study, we used an in vivo hilar clamp model in WT and A 1 R−/− mice to clarify a protective role of exogenous activation of A 1 R in lung IR injury.…”
Section: Discussionmentioning
confidence: 99%
“…Once the patient is back to the normal position, there is a possibility of ischemia reperfusion (IR) injury. This IR injury is well known and is mediated by superoxide and adenosine [6]. This cycle of events may result in further damage to the already compromised tissues and accelerate the disease with each and every episode of squatting.…”
Section: Discussionmentioning
confidence: 99%